Liberia : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver and Modification of Performance Criteria, and Financing Assurances Review; Staff Report; Informational Annex; and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Third Review for Liberia Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). The program remains on track. All performance criteria (PC) for end-June 2009 were met, except the PC on total revenue collection. IMF staff supports the authorities' request for a waiver on the basis that the deviation was temporary and did not jeopardize key program objectives. Structural reform commitments were largely met, albeit some with delays. The 2010 quantitative and structural reform program is appropriately ambitious.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet